A Retail Business Development Approach to Build a Designer Garment Brand Powered by Digital Marketing - Prasad, Krishna (Digital Repository of Theses - SSBM Geneva, 2024)
The fashion industry is a major contributor to the global economy and is even ahead of other prominent sectors like the automobile and energy sectors. Fashion brands are constantly adapting and reinventing their marketing and business strategies to approach emerging markets that are eager to consume fashion. Digital marketing has become an essential tool for these leading brands to communicate with their younger audiences. The challenges faced by fashion companies include digitization, a saturated market, consumer 2.0, influencers, and a new way of communicating fashion that is more social and interactive. The visual nature of the fashion industry makes social media the most effective medium for its dissemination. The appearance of Web 2.0 and the Social Media phenomenon have modified the basic pillars of business communication in the fashion sector. The following work aims to provide an in-depth study of this new scenario and its impact on the fashion industry. Digital marketing enables marketers to build relationships with customers through links, which can lead to increased brand awareness and loyalty. The use of different digital marketing tools and techniques, such as search engine optimization, social media marketing, and email marketing, can help companies create a strong brand image and increase their sales and revenue. The objective of this dissertation is to devise a novel Retail Business Growth Blueprint for a Designer Garment Brand that takes into account the authentic aspirations of consumers, augmented by harnessing the potential of Digital Marketing. A Designer Brand can amplify its presence in both physical and virtual spheres concurrently, and cater to the precise demands of a patron, rather than resorting to mass production and design thrust tactics. In this research, we shall delve into the exquisite world of Fatiz Bridal Emporio - a designer fashion house that graced the industry in 2010 as a quaint boutique nestled in the charming tier 2 city of Thrissur, Kerala. Our focus shall be on its remarkable evolution to a formidable brand, now boasting a presence in eight diverse cities that include the bustling metropolises of Mumbai, Chennai, and Hyderabad.